Evaluation of Regional Public Services Agency Implementation at Community Health Center in Mojokerto, East Java - Setyorini, Herin; Santosa, Agus; Dewi, Prima (Journal of Health Policy and Management, 2023)
Background: The phenomenon of the limitations of the community health center in managing budget expenditures can be seen when the beginning of the year cannot be realized. The limitations on spending on goods and services are also faced by community health centers every year. Changing the status of the community health center to regional public service agency (RPSA) allows the community health center to improve the quality of public health services. This study aimed to explore the evaluation of RPSA at community health center. Subject and Method: This was a qualitative study, with interviews with key informants. Discussions and interviews were conducted at community health center in the working area of Mojokerto district health office, Mojokerto, East Java, Indonesia from August to September, 2022. Participants: interview involved 27 informants, and 1 triangulated informant. The transcribed data were analyzed using content analysis.Results: A total of 27 Community Health Centers were ready to implement the Community Health Center RPSA because they have met the technical and administrative requirements for implementing Community Health Centers as RPSA. Government support is still lacking, seen from the absence of regional regulations after the establishment of the BLUDs that help the flexibility of the community health center. The support from the Mojokerto District Health Office is still considered low because 27 community health center stated that they had never been visited by the Health Office during their monitoring activities at the community health center.Conclusion: A total of 27 Community Health Centers are ready to implement the Community Health Center RPSA. Keywords: community health center, regional public services agecy, RPSA, Mojokerto.Correspondence:Herin Setyorini. Graduate School, STRADA Indonesia Institute of Health Sciences. Jl. Manila No.37, Tosaren, Pesantren, Kediri, 64123, East Java, Indonesia. Email: herinsetyorini07@-gmail.com. Mobile: +62 821-3248-2108.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.02.07